Effects of intermittent ractopamine HCl (paylean) use on pig growth performance in late finishing - C R Neill; C N Groesbeck; K R Brown; Robert D Goodband; Michael D Tokach; Jim L Nelssen; Joel M DeRouchey; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2005)
A total of 324 pigs (initially 149 lb) were used in a 56-d feeding trial to examine growth performance of pigs as affected by different ractopamine HCl (Paylean) regimens. There were four experimental treatments: A) the control diet fed for 56 d; B) the Paylean diet (9 g/ton) fed for 21 d, then control for 35 d; C) Paylean fed for 21 d, then control for 14 d, and then Paylean for 21 d; and D) control diet 35 d and then Paylean 21 d. Treatment C (feeding Paylean for 21 d, withdrawing it for 14 d, and re-feeding for 21 d) had the same overall affect on ADG and F/G as feeding Paylean for the last 21 d only. Weight gain was greater (P0.46) ADG and F/G, compared with pigs not previously fed Paylean. These results suggest that withdrawing Paylean for 14 d and re-feeding will have the same overall growth effect as feeding Paylean once.; Swine Day, 2005, Kansas State University, Manhattan, KS, 2005
Keywords: Swine day; 2005; Summary Publication of Report of Progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 964; Kansas Agricultural Experiment Station contribution; no. 06-63-S; Finishing pig; Paylean; Withdrawal; Swine